Non fu tutta colpa di padre Giacinto: spiegazioni troppo semplici e realtà (come sempre) complesse nel cammino di Oxalis pes-caprae L. dal Sudafrica al Mediterraneo (Altre Modernità, 2013)
Oxalis pes-caprae L. (= Oxalis cernua Thunb.) is a geophyte native to South Africa (Cape region) that was introduced in Europe in the second half of the eighteenth century as a cultivated plant. It is currently widely naturalized in many regions with mild climates all over the world and in several countries it has become a very noxious weed, due to its impressive capability of spreading through bulbils. According to a theory reported also in Pignatti’s Flora of Italy, all populations currently growing in Europe and the Mediterranean basin originated from a single plant introduced in the island of Malta by an English lady, who gave the plant collected in South Africa as a present to padre Giacinto, a monk and a botanist who founded the Botanical Garden in La Valletta. Starting from Malta, Oxalis pes-caprae would have subsequently spread along Mediterranean coasts and later in the whole continent. According to this theory, all European and Mediterranean populations would be merely parts of the same clone, made up of individuals genetically identical to the one originally arrived in Malta. An investigation based on original data mainly taken from herbarium specimens and bibliographic sources, definitely contradicts this theory, in favor of a more articulated explanation: the species invasion in the area is most likely the result of several different arrivals – both intentional and unintentional – occurred in different times and different places.